The effect of investment and financing decision, dividend policy and cost of capital on Indonesian firm value - Rindi Hariyanur; Ratna Septiyanti; Agus Zahron Idris (Asian Journal of Economics and Business Management, 2022)
This study aims to determine whether there is a relationship between investment decisions, funding decisions, dividend policies and the cost of capital with firm value. Business developments in the current era have made very significant progress which has made the competition increasingly fierce so that companies are required to be able to compete in order to survive and achieve company goals. To reduce errors in making decisions, companies need to pay attention to factors that can affect the value of the company. However, this topic is still being debated because some previous research results have different results. This study uses secondary data with a population of companies in the consumer goods industry sector and the agricultural industry sector listed on the Indonesia Stock Exchange from 2011 to 2020, the data obtained through the documentation method. The method used is purposive sampling and multiple linear regression analysis to determine the effect of the independent variable on one dependent variable that has a positive or negative relationship. The results showed that investment decisions, funding decisions, dividend policy and the cost of capital simultaneously have a significant effect on firm value. Partially, investment decisions and funding decisions have no significant effect on firm value, while dividend policy has a significant negative effect and the cost of capital has a significant positive effect on firm value. This finding shows that, in contrast to investment and funding decisions, which have not been able to directly or indirectly increase firm value, financial decisions involving dividend policies and the cost of capital can help companies achieve their longterm goals which are expected to be used as information material in decision making invest. The limitation of this research is that the sample used is only companies in the consumer goods industry and agriculture listed on BEI so that the results of the study cannot be generalized. it is recommended to use samples other than the two sectors so that the research results can be generalized, so as to provide more appropriate and comprehensive research results.